The role of human resources management in increasing the performance level of employees (An analytical study) - et.al, Salah Naser Mamdooh Rady, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this research, is to clarify the role of human resources management as an independent variable in raising the level of individuals' performance as a dependent variable, as it was applied in the field in the Ministry of Interior - General Directorate of Human Resources Management using the descriptive analytical approach.